Bahasa inggris - Riska Daulima; Fitriani R. Blongkod; Srikit S. Nurkamiden (LPPM Universitas Bina Mandiri Gorontalo, 2022)
The purpose of this study is to determine the Triglyceride (TG) levels in obese patients. The research is conducted in a descriptive quantitative approach. Primary data in the form of research findings on TG levels in obese patients and secondary data in the form of data from the literature, books, questionnaires, books, and medical records were used. Purposive sampling was used with a sample size of 30 participants.The results showed that of 30 obese patients, 27 (90%) had abnormal TG levels. While 3 persons (10%), had normal TG levels. The factors that had the greatest influence on the level of TG in obese patients were their physical features (body mass index/BMI) and dietary habits (number of calories). The study concluded that 90% of obese patients had normal triglyceride levels, while 10% had abnormal levels. Suggestions for obese people to manage and control their triglyceride levels on a regular basis, as well as engage in other activities that can help prevent obesity.